Revealing experiences hidden from history: Through the eyes of women travelers in the Eastern Mediterranean and Black Sea regions in the 17th to early 20th centuries - Irene Kamberidou (Port cities and maritime routes in Eastern Mediterranean and Black Sea 18th–21st centuries, 2020)
A plethora of scholarly works have been published on male Western travelers in the Eastern Mediterranean and Black Sea regions, however the accounts of female travel writers drawing attention to experiences hidden from history could also be a welcome addition or an alternative discourse with a gender perspective. Motivated by a cross-examination of the original accounts of 240 Western women travelers in Ottoman territories in the 17th to 19th centuries, showing that over 6000 women travelled and experienced the Orient (Kamberidou 2017, 2016, 2015a), this paper continues the research, examining women’s contributions in times of conflict. As early as the 17th century, women have been going from one corner of the world to the other witnessing historic events, war and conflict, religious persecutions, pillaging and the removal or destruction of antiquities, and writing about it. The firsthand accounts of 252 European and American women travelers of the 17th to early 20th centuries in Asia Minor, Cyprus, Syria, Egypt, Greece and other Ottoman occupied territories confirm that thousands of women travelled and witnessed historic events. Women from Great Britain, France, Germany, Switzerland, Sweden, Austria and America explored, visited, resided as permanent residents, worked or served as volunteers, missionaries, educators, nurses, artists, governesses, ladies in waiting and servants of the western or eastern elite in different regions of the Ottoman Empire. This paper begins with a brief discussion on women travelers, subsequently focusing on 19th Century accounts regarding women’s contributions in times of conflict, exclusively from archival sources: the narratives of women volunteers, nurses, care givers and morale builders during the Crimean War (1853-1856), when the colonial experience encouraged female engagement. The accounts of English, French and German women who cared for the soldiers in the military hospitals of Constantinople and its environs reveal that women played key roles in social care, public health and hospital management, showing initiative and innovation in crisis management. The female accounts describe the British military and naval hospitals; the nurses duties and hardships (1,500 patients per 3 women: two lady volunteers and one nurse); the hundreds of women who followed their husbands to war; the demoralizing barrack system; the degrading social status and abuse of the English soldier’s wife and babies; the elevated status and protection enjoyed by the French soldier’s wife; the French military system. The female narratives argue that the French soldiers, as opposed to the English, are educated, industrious, productive and creative, adding to the general good. They spotlight the superiority of the French soldiers as regards their manners, morals, courtesy, organizational skills, patriotism and especially their respect and treatment of women. Keywords:  Gender, Women, War, Female accounts, Volunteerism